ROLE OF PANCHAYATI RAJ INSTITUTIONS IN EMPOWERING WOMEN: A STUDY OF RURAL AREAS IN INDIA - Yakar, Bar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In order to evaluate the critical role that Panchayati Raj Institutions (PRIs) play in empowering women in rural India, this research does a thorough comparative analysis. As local self-government organizations required by the constitution, PRIs are essential to the decentralization of government and the advancement of social inclusion. This study assesses how much PRIs in various rural areas of the nation support women’s social empowerment, economic development, and involvement in decision-making processes. The study looks at the dynamics of PRIs in several states, highlighting obstacles and achievements and providing insightful information for the creation of policies and programmes promoting women empowerment.